The effect of electroslag remelting on the cleanliness of CrNiMoWMnV ultrahigh-strength steels - Ali M.; Porter D.; Kömi J.; Heikkinen E.P.; Eissa M.; El Faramawy H.; Mattar T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The cleanliness of ultrahigh-strength steels (UHSSs) without and with electroslag remelting (ESR) using a slag with the composition of 70% CaF2, 15% Al2O3, and 15% CaO was studied. Three experimental heats of UHSSs with different chemical compositions were designed, melted in an induction furnace, and refined using ESR. Cast ingots were forged at temperatures between 1100 and 950°C, air cooled, and their non-metallic inclusions (NMIs) were characterized using field emission scanning electron microscopy and laser scanning confocal microscopy. Thermodynamic calculations for the expected NMIs formed in the investigated steels with and without ESR were performed using FactSage 7.2 software while HSC Chemistry version 9.6.1 was used to calculate the standard Gibbs free energies (ΔG°). As a result of ESR the total impurity levels (TIL% = O% + N% + S%) and NMI contents decreased by as much as 46 % and 62 %, respectively. The NMIs were classified into four major classes: oxides, sulphides, nitrides, and complex multiphase inclusions. ESR brings about large changes in the area percentages, number densities, maximum equivalent circle diameters, and the chemical composition of the various NMIs. Most MnS inclusions were removed although some were re-precipitated on oxide or nitride inclusions leading to multiphase inclusions with an oxide or nitride core surrounded by sulphide, e.g. (MnS.Al2O3) and (MnS. TiN). Also, some sulphides are modified by Ca forming (CaMn)S and CaS.Al2O3. Some nitrides like TiN and (TiV)N are nucleated and precipitated during the solidification phase. Al2O3 inclusions were formed as a result of the addition of Al as a deoxidant to the ESR slag to prevent penetration of oxygen to the molten steel.